Interpreting UNDRIP: Exploring the Relationship Between FPIC, Consultation, Consent, and Indigenous Legal Traditions - Warnock, Jeffrey (Scholarship@Western, 2021)
This thesis addresses an interpretive question at the heart of the discourse surrounding the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP); the meaning of the principle of Free, Prior, and Informed Consent (FPIC). It argues that interpreting and implementing UNDRIP and specifically the articles requiring FPIC needs to be done in a way that meaningfully engages with and incorporates the laws of Indigenous peoples (Indigenous Legal Traditions or ILTs). This thesis explores why it is essential to discuss UNDRIP through the lens of ILTs, explores the scholarship and major interpretive schools of thought regarding FPIC, and concludes that at least within the Canadian context, they have not meaningfully engaged with ILTs. This thesis also addresses the ways in which Canada’s current approach to consultation (the duty to consult) engages with ILTs. It concludes with an examination of the impact that Anishinaabe law can have on the interpretation of FPIC.